PERAN CITRA MEREK MEMEDIASI PENGARUH KEWAJARAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK ONLINESHOP ZALORA DI DENPASAR - Wahyuni, Ni Putu Lely; Rahanatha, Gede Bayu (E-Jurnal Manajemen; Vol 9 No 2 (2020)DO - 10.24843/EJMUNUD.2020.v09.i02.p19, 2020)
Online shopping is one of trend that is growing rapidly nowadays. Now the technological advancement supported rapid growth of the online shopping and make it easier for consumer to shopping. Consumer is more selective to make purchase decision, consumer tend to chose product that have good brand image and compatible price. This research aims to find out the influence between price and purchase decision with brand image as a mediation variable. Realizing the potential of market online especially the fashion product, then this research raising the topic with price fairness, brand image and purchase decision as the objects. Respondents are them who have been online purchasing. The survey conducted by spreading questionnaire than measured by likert’s scale. Data analyzed by path analysis and sobel test. The result of this research showed than variable brand image capable of being mediated the influence between price fairness and consumer purchase decision. Keywords : price fairness, brand image, purchase decision